Chitosan-Based Multifunctional Platforms for Local Delivery of Therapeutics - Hong, Seong-Chul (Mar Drugs, 2017)
Chitosan has been widely used as a key biomaterial for the development of drug delivery systems intended to be administered via oral and parenteral routes. In particular, chitosan-based microparticles are the most frequently employed delivery system, along with specialized systems such as hydrogels, nanoparticles and thin films. Based on the progress made in chitosan-based drug delivery systems, the usefulness of chitosan has further expanded to anti-cancer chemoembolization, tissue engineering, and stem cell research. For instance, chitosan has been used to develop embolic materials designed to efficiently occlude the blood vessels by which the oxygen and nutrients are supplied. Indeed, it has been reported to be a promising embolic material. For better anti-cancer effect, embolic materials that can locally release anti-cancer drugs were proposed. In addition, a complex of radioactive materials and chitosan to be locally injected into the liver has been investigated as an efficient therapeutic tool for hepatocellular carcinoma. In line with this, a number of attempts have been explored to use chitosan-based carriers for the delivery of various agents, especially to the site of interest. Thus, in this work, studies where chitosan-based drug delivery systems have successfully been used for local delivery will be presented along with future perspectives.